100 Percent Population Testing and Concerns of Auditors With Limited Liability Exposure: Evidence From Retail Investors - Wilson, Reginald; Revels, Brock (Journal of Accounting and Finance, 2023)
This study investigates whether the type of evidence collected during an audit reduces retail investors concerns of CPA firms whose liability exposure is limited during an audit engagement. This study is motivated by calls for further research pertaining to the benefits and effectiveness realized by the use of big data during the audit engagement. Retail investors who responded to a 2 x 2 experiment did not perceive CPA firms’ independence to be impaired, regardless of the audit methodology used to gather audit evidence (100 percent population testing versus traditional sampling). These results are useful to accounting lawmakers who previously expressed concern that a reduction of liability would impair auditors’ judgement during the audit. Similarly, these results may assist accounting lawmakers in deciding whether or how to change auditing standards to reflect the benefits of big data in auditing. This study was approved by the Institutional Review Board.